ANALISIS BUTIR SOAL HOTS PILIHAN GANDA PADA MATA PELAJARAN AKUNTANSI FASE F MELALUI PROGRAM KOMPUTER ANATES V4 - Annara Nathania Sabella; Linda Puspitasari; Shafira Aulia Rahma; Salsabila Nur Faidah; Chelsie Nur Oktavia; Vivi Pratiwi; Luqman Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study evaluates the quality of Higher Order Thinking Skills (HOTS) assessment instruments for Phase F Accounting. The core problem identified is the limited teacher capacity for conducting qualitative item analysis manually, which risks compromising assessment validity. Employing a quantitative descriptive method, this research analyzes response data from 45 exam questions to evaluate their psychometric characteristics, including validity, reliability, difficulty index, discriminating power, and distractor effectiveness using Anates V.4 software.The empirical findings confirm that 76.67% of the items meet validity criteria with a high overall reliability coefficient. The majority of the items were of moderate difficulty. However, an in-depth analysis of the distractors revealed the ineffectiveness of several options, indicating a need for systematic revision.A key practical implication of this study is the validation of Anates V.4 as a technological solution for enhancing the efficiency of item bank analysis. The original contribution of this research lies in its computational analysis of HOTS items for Phase F Accounting, with a specific focus on distractor effectiveness—an analytical dimension often overlooked in similar literature. This focused approach provides a critical and replicable framework for improving the quality of HOTS-based assessments.